2020
DOI: 10.3390/jdb8040030
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes, Developmental Basis, and Genetics of Pierre Robin Complex

Abstract: The phenotype currently accepted as Pierre Robin syndrome/sequence/anomalad/complex (PR) is characterized by mandibular dysmorphology, glossoptosis, respiratory obstruction, and in some cases, cleft palate. A causative sequence of developmental events is hypothesized for PR, but few clear causal relationships between discovered genetic variants, dysregulated gene expression, precise cellular processes, pathogenesis, and PR-associated anomalies are documented. This review presents the current understanding of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 109 publications
0
17
0
Order By: Relevance
“…We first examined known craniofacial disorder associations of genes that are downregulated upon SOX9 depletion, also considering the relation to PRS, which is caused by heterozygous LoF coding or noncoding mutations at the SOX9 locus. However, mutations in genes other than SOX9 have also been associated with PRS-like micrognathia phenotypes in either humans or mice (reviewed in 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first examined known craniofacial disorder associations of genes that are downregulated upon SOX9 depletion, also considering the relation to PRS, which is caused by heterozygous LoF coding or noncoding mutations at the SOX9 locus. However, mutations in genes other than SOX9 have also been associated with PRS-like micrognathia phenotypes in either humans or mice (reviewed in 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…We first examined known craniofacial disorder associations of genes that are downregulated upon SOX9 depletion, also considering the relation to PRS, which is caused by heterozygous LoF coding or noncoding mutations at the SOX9 locus. However, mutations in genes other than SOX9 have also been associated with PRS-like micrognathia phenotypes in either humans or mice (reviewed in 46 ). We observed that SOX9-dependent genes associated with dominant (likely more dosage-sensitive) craniofacial disorders unrelated to PRS had lower ED50 values than genes not associated with craniofacial disorders, while genes associated with recessive (likely less dosage-sensitive) disorders had higher ED50 values (Fig.…”
Section: Ro Chondrogenic Genesmentioning
confidence: 99%
“…ERK1/2 is the main effector of FGF signaling [ 99 , 100 ]. Disruption of the ERK/MAPK pathway in neural crest cells of Wnt1-Cre ; Erk2 fl/fl mice causes cleft palate, malformed tongue, micrognathia and mandibular asymmetry [ 101 ], similar to the Pierre Robin complex, triad of mandibular dysmorphology, glossoptosis, and respiratory obstruction with or without cleft palate [ 102 ]. However, when Erk2 deletion is restricted to the palatal mesenchyme in Osr2-Cre ; Erk2 fl/fl mice, cleft palate was not observed, indicating that the cleft palate in Wnt1-Cre ; Erk2 fl/fl mice is a secondary defect.…”
Section: Molecular and Cellular Mechanismsmentioning
confidence: 99%
“…Most of the cleft lip and/or palate are nonsyndromic and multifactorial (Jakobsen et al, 2007). Pierre Robin sequence (PRS) is a clinical entity characterized by micrognathia/retrognathia leading to glossoptosis, respiratory obstruction, and a U-shaped cleft palate (Hanson and Smith, 1975; Motch Perrine et al, 2020). Microganthia in PRS can be caused by extrinsic, intrinsic, or neuromuscular abnormalities.…”
Section: Introductionmentioning
confidence: 99%